2019
DOI: 10.1371/journal.pone.0225268
|View full text |Cite
|
Sign up to set email alerts
|

Front-of-pack nutritional labels: Understanding by low- and middle-income Mexican consumers

Abstract: Front-of-pack labeling is a cost-effective strategy to decrease population consumption of sodium, sugar, saturated fat, total fat, and trans-fatty acids, considered critical nutrients for chronic disease. Our main objective was to explore the subjective understanding of labels that are currently used internationally among low- and middle-income Mexican consumers. We performed two phases of 10 focus groups with adolescents (13–15 y), young adults (21–23 y), mothers of children 3–12 y, fathers of children 3–12 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 43 publications
(61 reference statements)
7
53
0
1
Order By: Relevance
“…In this article, results for consumer understanding showed that interpretive FoPLs had greater potential than purely informative systems to improve the capacity of Italian consumers to correctly rank the nutritional quality of foods. This finding is consistent with the results of studies conducted in other countries [27][28][29][30][31][32][33][34][35], and especially European countries [19,[36][37][38][39][40], with similar trends in FoPL outcomes identified in high-and middle-income countries. Moreover, it appears that summary indicators with a graded scale (i.e., Nutri-Score, HSR) are easier for consumers to understand as they showed the best results in the ranking tasks.…”
Section: Discussionsupporting
confidence: 92%
“…In this article, results for consumer understanding showed that interpretive FoPLs had greater potential than purely informative systems to improve the capacity of Italian consumers to correctly rank the nutritional quality of foods. This finding is consistent with the results of studies conducted in other countries [27][28][29][30][31][32][33][34][35], and especially European countries [19,[36][37][38][39][40], with similar trends in FoPL outcomes identified in high-and middle-income countries. Moreover, it appears that summary indicators with a graded scale (i.e., Nutri-Score, HSR) are easier for consumers to understand as they showed the best results in the ranking tasks.…”
Section: Discussionsupporting
confidence: 92%
“…The GDA label was the control group because they are required to appear on the FOP of food products in Mexico.Ecuadorian Multiple Traffic Lights (MTL), color coded (red, yellow, and green, respectively), including text descriptors to indicate high, medium, or low content of total fat, sugar and salt.Chilean Warning Labels (WL) in red, indicating when a product exceeds the content of energy, sodium, total sugar and saturated fat. We decided to put the WL in red because previous work by our research group demonstrated this color increased label acceptability [31].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…3) Chilean Warning Labels (WL) in red. Red WL were used because previous work in Mexican consumers has demonstrated this color increased label acceptability [29] and discouragement from wanting to consume unhealthy drinks [30], both of which are predictors of the effectiveness of FOP labels [5,25,31] Intervention After allocation, participants viewed a video explaining how to correctly interpret the assigned label (the prompt to make their choices with specific nutrients-to-limit in mind). We used official videos used in each country (i.e.…”
Section: ) Ecuadorian Multiple Traffic Lights (Mtl)mentioning
confidence: 99%